2019
DOI: 10.2187/bss.33.12
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity induces vertebrae and otolith deformation in medaka fish

Abstract: Teleost fish live under a constant force derived from gravity, with hard tissues playing important roles to help maintain body balance. However, the mechanism of hard tissue formation induced by gravity remains unclear. To examine the effects of gravity in aquatic animals, we performed experiments with medaka fish reared in a hypergravity environment, in which the force of gravity exceeded that present on the surface of the Earth, and analyzed hard tissue formation. Medaka fish were reared for 6 months under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Using a centrifuge designed for small-fish rearing, the effect of hypergravity on medaka reared for 6 months under normal gravity (1 g ) or under gravity, approximately 5 times normal (5 g ) was investigated 45 . Micro-computer tomography analysis revealed that although the fish were able to maintain body posture and position, hypergravity gradually induced vertebral curvature towards the dorsal side and asymmetric formation of otoliths in which the cross-sectional area was increased.…”
Section: Recent Jaxa Space Missions Related To Muscle and Bonementioning
confidence: 99%
“…Using a centrifuge designed for small-fish rearing, the effect of hypergravity on medaka reared for 6 months under normal gravity (1 g ) or under gravity, approximately 5 times normal (5 g ) was investigated 45 . Micro-computer tomography analysis revealed that although the fish were able to maintain body posture and position, hypergravity gradually induced vertebral curvature towards the dorsal side and asymmetric formation of otoliths in which the cross-sectional area was increased.…”
Section: Recent Jaxa Space Missions Related To Muscle and Bonementioning
confidence: 99%
“…This situation was tested on swordtail fish and medaka otoliths (Anken et al, 1998;Ijiri et al, 2003;Brungs et al, 2011;Anken et al, 2016) and larvae bone development (Aceto et al, 2015;Chatani et al, 2015), but its effects on early ontogeny (hatching capability) are as yet poorly described. A recent research showed that six month exposition at 5 g can induce vertebral curvatures and asysmetric otoliths (Chatani et al, 2019). However, the duration of exposure to hypergravity during a launch to the Moon or Mars will be about 10 min, the time to extract the embryos from the Earth's attraction.…”
Section: Studying the Feasibility Of Sending Aquaculture Fish Embryos To The Moon: The Lunar Hatch Programmentioning
confidence: 99%
“…Hatched medaka larvae from Cab or TRAP-GFP/ Osterix-DsRed double transgenic lines were placed in bottles (Nunc EasyFlask 75 cm 2 , Thermo Scientific) containing 200 ml of rearing water, then in an incubator for three days with light blocked. For the 5g condition, that was generated by spinning with a centrifuge (LIX-140SP, Tomy Seiko Co., Ltd) at 160 rpm (Chatani et al 2019).…”
Section: Rearing Larvae In Watermentioning
confidence: 99%
“…The 1g control group was placed stationary on a desk. For the 5g (5.29 times greater than normal gravity) group, that was generated by centrifuge spinning at 160 rpm (Chatani et al 2019), while the s-μg group was rotated in a clinostat device (Zeromo CL-100, Kitagawa). Larvae were removed from the agarose gel after three days and signals indicating calcification were observed using a fluorescence microscope (M205FA, Leica).…”
Section: Rearing Larvae In Agarose Gelmentioning
confidence: 99%
See 1 more Smart Citation